Perancangan Konten Video Berbasis Media Sosial sebagai Upaya Meningkatkan Engagement pada Usaha Jilbab Ansania Semarang - Muhamad Arif Aulia Ardana; Aris Sarwo Nugroho (UNIVERSITAS STEKOM, 2026)
The development of digital technology has encouraged the use of social media as an efficient promotional tool for businesses, particularly micro, small, and medium enterprises (MSMEs). One type of content frequently used is video, as it can convey messages visually and engage audiences. However, inadequate content design can lead to low engagement rates on social media. This study aims to design social media-based video content to increase engagement at the Jilbab Ansania Semarang business. The method used in this research is Research and Development (R&D) with a Design and Development (D&D) approach, which includes the stages of needs analysis, design, development, implementation, and evaluation. Data collection techniques include observation, interviews, documentation, and literature review. The research results show that videos tailored to the target audience and social media platform can increase engagement. This is evident in the increase in likes, comments, shares, and views. Therefore, creating video content focused on social media has proven effective as a digital promotional tool to increase engagement for the Jilbab Ansania Semarang business.